Meningkatkan Kreativitas Dan Hasil Belajar Siswa Muatan PPKN Menggunakan Model Pemimpin Pada Siswa Kelas V SDN Antasan Besar 1 Banjarmasin - Fitri Augina Izmi; Sakerani (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research was conducted because of problems in the field, namely activity, creativity and student learning outcomes with low PPKn content. The research aims to provide a description of the activities of teachers, students and their creativity, as well as improving learning outcomes. The researcher used a qualitative approach with a type of classroom action research conducted in 4 meetings. Researchers selected 18 class V students at SDN Antasan Besar 1 Banjarmasin in the 2023/2024 academic year. There are two types of data collected, namely qualitative in the form of observations of teacher and student activities, while quantitative data is obtained from creativity tests and learning outcomes in the form of individual and group tests. The results of the research showed that at meeting 1 the teacher achieved 63% of the "good" criteria, improving to meeting 4 reaching 88% of the "very good" criteria. Student activity at meeting 1 was only 50% within the "quite active" criteria, improving at meeting 4 reaching 89% to the "very active" criteria. Student creativity at meeting 1 received 44% of the "quite creative" criteria, while at meeting 4 it reached 89% of the "very creative" criteria. Likewise, the learning results at meeting 1 were classically 50% of students completed and improved at meeting 4 reaching 89% of students who completed.